THE ANALYSIS OF METHODOLOGICAL SPECTRUM OF LEGAL RESEARCH - Levičev, Vitalij (Teisė, 2015)
In comparison with theory of law, legal methodology improvidently deserves much less attention which undoubtedly effects overall quality of legal research. In this article we are trying to fill the gulf between theory and methodology of law by analyzing the methodological spectrum of legal research. Not only separate fields of legal methodology are subject to comprehensive analysis, but also the wholeness of the overall spectrum receives proper attention. Legal reality is enormously heterogeneous and its origins consist of at least three interrelated aspects: formal law, real law and ideal law. Legal methodology diverges accordingly: doctrinal research of formal law, socio-legal research of real law and axiological-ethical research of ideal law. Research showed us, that all of these methodological branches are closely interrelated and should be involved in the development of the theory of methodological synthesis. Any of these three is not self-sufficient and without any one of them the thorough research of legal reality is not possible.